Modeling multi-contact point physical interaction between the anthropomorphic finger and soft robotic exo-digit for wearable rehabilitation robotics applications - Alam, Umme Kawsar; Shedd, Kassidy; Kirkland, Joshua; Yaksich, Kayla; Haghshenas-Jaryani, Mahdi (Frontiers in Robotics and AI, 2023)
This paper presents a quasi-static model for the motion of a soft robotic exo-digit while physically interacting with the anthropomorphic finger model for physical therapy. Quasi-static analytical models were developed for modeling the motion of the soft robot, the anthropomorphic finger, and their coupled physical interaction. An intertwining of kinematics and quasi-static motion was studied to model the distributed (multiple contact points) interaction between the robot and a human finger model. The anthropomorphic finger was modeled as an articulated multi-rigid body structure with multi-contact point interaction. The soft robot was modeled as an articulated hybrid soft-and-rigid model with a constant bending curvature and a constant length for each soft segment. A hyperelastic constitute model based on Yeoh's 3rd order material model was used for modeling the soft elastomer. The developed models were experimentally evaluated for 1) free-motion of individual and fully integrated soft actuators and 2) constrained motion of soft robotic exo-digit and the anthropomorphic finger model. Simulation and experimental results were compared for performance evaluations. The theoretical and experimental results agreed for free motion and the deviation between the constrained motion were in the range of the experimental errors. The outcomes also provided an insight into the importance of considering lengthening for the soft actuators.